Squid Resource Management (Loligo sp.) with a Bioeconomic Approach in Belitung Regency - Ansori, Ariqoh; Adibrata, Sudirman; Aisyah, Siti (PELAGICUS, 2022)
Squid is one of the catches that contributes a lot to the value of marine fishery production in the Belitung Regency. In addition, squid is one of the fish resources that are economically valuable. Until now, all squid production in Indonesia comes from catches in nature. This means that products derived from cultivation do not yet exist. If only relying on the effort of the results of the capture alone, it is not impossible that one day there will be overfishing. The purpose of this study is to know the bioeconomic aspects of squid resources in the Belitung Regency. Research has been carried out in the waters of the Belitung Regency of Bangka Belitung Islands Province, with research locations in 3 (three) sub-districts that become fishing bases for squid fisheries, namely Sijuk, Membalong, and Tanjung Pandan districts. The method used is Purposing Sampling with case studies taking primary data from interviewed fishermen directly and secondary data from the Belitung district marine and fisheries service and Tanjung Pandan Regency VAT. Gordon Schaefer's Bioeconomics Analysis yields a CMSY value of 34.522 tons/year and an EMSY of 16.105 ships/year.  MEY condition was obtained at the time of CMEY value of 34.327 tons/year and EMEY value of  14.893 units of ships/year. The condition of OAE was obtained at the time of the COAE value of 9.616 tons/year and the EOAE value of 29.785 units of ships/year. The squid utilization rate in Belitung Regency has experienced overfishing in 2018 by 220%.